Variation in vegetation composition, biomass production, and carbon storage in ridge top forests of high mountains of Garhwal Himalaya. (17th February 2016) - Sharma, C. M.; Mishra, Ashish K.; Krishan, Ram; Tiwari, O. P.; Rana, Y. S.
Abstract: The present study was aimed to anticipate how forest composition, regeneration, biomass production, and carbon storage vary in the ridge top forests of the high mountains of Garhwal Himalaya. For this purpose five major forest types—(a) Pinus wallichiana, (b) Quercus semecarpifolia, (c) Cedrus deodara, (d) Abies spectabilis, and (e) Betula utilis mixed forests—were selected on different ridge tops in the Bhagirathi Catchment Area of the Uttarkashi District of Garhwal Himalaya. The highest species richness (10 species) and stand density (804 ± 184.5 stems ha −1 ) were recorded in Abies spectabilis forests, whereas lowest species richness (4 species) and species density (428 ± 144.7 stems ha −1 ) were found in Quercus semecarpifolia forests. The total basal cover (TBC) values were maximum (91.1 ± 24.4 m 2 ha −1 ) in Cedrus deodara forests and minimum (26.5 ± 11.7 m 2 ha −1 ) in Pinus wallichiana forests. The highest total biomass density (TBD) (464.2 ± 152.5 Mg ha −1 ) and total carbon density (TCD; 208.9 ± 68.6 Mg C ha −1 ) values were recorded for Cedrus deodara forests; however, lowest TBD (283.4 ± 74.8 Mg ha −1 ) and TCD (127.5 ± 33.7 Mg C ha −1 ) values for Quercus semecarpifolia forests. Our study suggests that Abies spectabilis -dominated forests should be encouraged for biodiversity enrichment and reducing carbon emissions on ridge top forests of high mountains.